Peran Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Dalam Menanggulangi Perkawinan Anak Di Kota Pontianak - Kharista, Marisa; Hazilina, Hazilina; Febriany, Tri Atika (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
This study aims to identify and analyze the role of the Office of Women's Empowerment and Child Protection (DP3A) of Pontianak City in addressing child marriage. Child marriage remains a concerning social issue due to its negative impact on children's rights, education, and future, especially for girls. In Pontianak, major contributing factors include economic conditions, cultural norms, and lack of awareness regarding the importance of education. This research employs an empirical method with data collected through interviews, observation, and documentation. The findings reveal that DP3A has implemented various strategies such as community and school outreach, education on the harmful effects of child marriage, assistance for victims, and collaboration with related institutions. Despite strong commitment, program implementation faces several challenges, including limited human and financial resources, as well as low public participation. Therefore, cross-sector collaboration and increased community awareness are essential to achieve more effective and sustainable efforts in preventing child marriage. Keywords: DP3A, child marriage, Pontianak, government role, child protection